High-sensitivity observations of molecular lines with the Arecibo Telescope. Issue 2 (26th June 2020) - Tan, W S; Araya, E D; Lee, L E; Hofner, P; Kurtz, S; Linz, H; Olmi., L
ABSTRACT: We report on one of the highest sensitivity surveys for molecular lines in the frequency range 6.0–7.4 GHz conducted to date. The observations were done with the 305- m Arecibo Telescope toward a sample of 12 intermediate-/high-mass star-forming regions. We searched for a large number of transitions of different molecules, including CH3 OH and OH. The low rms noise of our data ($\sim \!5\, $  mJy for most sources and transitions) allowed detection of spectral features that have not been seen in previous lower sensitivity observations of the sources, such as detection of excited OH and 6.7 GHz CH3 OH absorption. A review of 6.7 GHz CH3 OH detections indicates an association between absorption and radio continuum sources in high-mass star-forming regions, although selection biases in targeted projects and low sensitivity of blind surveys imply incompleteness. Absorption of excited OH transitions was also detected toward three sources. In particular, we confirm a broad 6.035 GHz OH absorption feature in G34.26+0.15 characterized by an asymmetric blueshifted wing indicative of expansion, perhaps a large-scale outflow in this H ii region.